(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2016)
As a field of theoretical and practical interest, business ethics in its present form exists since about twenty five years. During that period, it has known developments that can aptly be presented as successive phases. Which developments, which phases? Can we reconstruct them in such a way that we get hold of the actual situations, and of the achievements, eventual lacunae, and the subsequent requirements implied in them? Those are the questions that I take as a lead. Having witnessed the developments primarily on the European scene, it is the Old Continent, first and foremost, that will provide me with a map for my search, the United States serving occasionally as a clarifying background.